2021
DOI: 10.1016/j.jtauto.2021.100105
|View full text |Cite
|
Sign up to set email alerts
|

Killing three birds with one BPI: Bactericidal, opsonic, and anti-inflammatory functions

Abstract: Bactericidal/permeability-increasing protein (BPI) is an anti-microbial protein predominantly expressed in azurophilic granules of neutrophils. BPI has been shown to mediate cytocidal and opsonic activity against Gram-negative bacteria, while also blunting inflammatory activity of lipopolysaccharide (LPS). Despite awareness of these functions in vitro, the magnitude of the contribution of BPI to innate immunity remains unclear, and the nature of the functional role of BPI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 129 publications
0
13
0
2
Order By: Relevance
“…Together these results are in agreement with previous studies demonstrating that BPI displays anti-inflammatory properties in both in vitro and in vivo experimental models. For instance, a recent study reported enhanced neutrophil recruitment and inflammatory cytokines in BPI-deficient mice infected with Pseudomonas aeruginosa, which were corrected after administration of exogenous BPI [ 21 ]. In addition, it was shown that BPI prevents TNF secretion by human PBMC in response to LPS in a dose-dependent manner [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together these results are in agreement with previous studies demonstrating that BPI displays anti-inflammatory properties in both in vitro and in vivo experimental models. For instance, a recent study reported enhanced neutrophil recruitment and inflammatory cytokines in BPI-deficient mice infected with Pseudomonas aeruginosa, which were corrected after administration of exogenous BPI [ 21 ]. In addition, it was shown that BPI prevents TNF secretion by human PBMC in response to LPS in a dose-dependent manner [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although the anti-inflammatory action of BPI is well known, this effect has only been demonstrated in the presence of bacterial infections so far. Indeed, this protein exerts an antimicrobial activity by damaging bacterial membranes, neutralizing endotoxin, and exhibiting opsonic function [ 9 , 21 ]. Otherwise, in our experiments, we used MSU or CPP crystals, which are pathogenic but not infectious agents, thus suggesting for the first time that BPI can also exert an anti-inflammatory activity in sterile inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals display a wide array of membrane‐targeting antimicrobial proteins, but only representatives with activity against at least some of the ESKAPE Gram‐negatives, and/or publications regarding their therapeutic potential are discussed here (Table 3 , Fig. 1 ): Bactericidal/permeability increasing protein (BPI) and related proteins, Group IIA secretory Phospholipase A 2 (GIIA sPLA2), and the surfactant‐associated proteins SP‐A and SP‐D, which have been reviewed recently not only in terms of their antimicrobial power but also for other interesting immunomodulatory features and implications (Floros et al ., 2021 ; Letsiou, Htwe & Dudek, 2021 ; Theprungsirikul, Skopelja‐Gardner & Rigby, 2021 ). Some antimicrobial proteins are not addressed here, either because they have poor (or untested) activity against ESKAPE Gram‐negative pathogens [for example, human skin chemerin (Banas et al ., 2013 )], or because there is uncertainty about their mechanistic action.…”
Section: Bacterial Envelope‐targeting Mammalian Humoral Innate Immuni...mentioning
confidence: 99%
“…The recombinant N-terminal fragment of human BPI (rBPI21) was shown to be highly effective against MDR Gram-negative bacteria including MDR Pa (15). However, anti-neutrophil cytoplasmic autoantibodies directed against BPI (BPI-ANCA) found in up to 83% of CF patients (16) inhibit the bactericidal function of BPI (17,18). Coherently, BPI-ANCA correlate with increased colonization with Pa (19), impaired lung function and poor prognosis (20).…”
Section: Introductionmentioning
confidence: 99%